Lifetime reliability analysis of concrete columns damaged by reinforcement corrosion - Chen, Hua-Peng; Jiang, Yu; Xiao, Linfa; Liu, Jiahua (Frontiers in Materials, 2022)
Rebar corrosion caused by chloride ion ingression is a critical factor leading to performance deterioration of in-service reinforced concrete (RC) structures exposed to aggressive environments. This paper presents a new method to evaluate the concrete crack growth, the bearing capacity degradation and the lifetime performance deterioration for the corroded RC columns under small eccentric compression. By analyzing the material degradation mechanism of the corroded RC structures, an effective method is proposed to predict the concrete crack growth and to estimate the residual bearing capacity of the corroding eccentrically loaded RC columns. Then, the concrete crack width and the load-bearing capacity deterioration rate are selected as structural performance indicators to assess the lifetime performance of the corroding RC columns. The stochastic gamma process is adopted for simulating the evolution of structural performance indicators and estimating lifetime failure probability and the remaining useful life of the corroding structures. Finally, a numerical example is given to demonstrate the effectiveness of the proposed methods for the lifetime performance assessment of the corroding columns. The obtained results show that the residual bearing capacity and the lifetime performance of the corroding RC columns can be significantly affected by rebar corrosion level, load condition and in-service environments.